A macroscopic model of the compaction process during compression molding of carbon fiber sheet molding compounds. (June 2023) - Doppelbauer, Leonhard K.; Rienesl, Konrad; Stelzer, Philipp S.; Zulueta, Kepa; Chang, Li-Yang; Major, Zoltán
Abstract: Modeling the compressive behavior of carbon fiber sheet molding compounds (CF-SMC) during processing can be a difficult task. This is due to the pronounced porosity of SMC materials, which cannot be adequately reproduced by currently available compressibility models (also called pvT models). Consequently, a macroscopic non-isothermal compression model was developed in this study, which is easy to evaluate and suitable for numerical compression molding simulations. Furthermore, a pvT dilatometer was developed to measure the compressibility of an industrial CF-SMC material. The compression model was calibrated with the measured data and implemented in a commercially used compression molding simulation software. The analytical model accurately describes the compaction behavior of the CF-SMC and its applicability in numerical simulations has been demonstrated. Highlights: A macroscopic compaction model was developed for the pvT behavior of CF-SMCs. The model describes bulk behavior and reduction of porosity during compaction. Measurements with the designed dilatometer show good agreement with the model. Implementation in the commercial process simulation code Moldex3D is demonstrated. Numerical simulations of isothermal and non-isothermal compaction are presented.